Obtaining of nanocatalizers for low-temperature conversion of oxide carbon (CuO/ZnO/Al2O3) with reduced copper content - Usmanova, M.M.; Dolgov, V.V.; Ashurov, N.R.; Rashidova, S.Sh.; Dadahodzhaev, T. (KSU publ., 2020)
The main goal of the work was to reduce the content of copper (in terms of copper (II) oxide) in the composition of the conversion catalyst, and to preserve high catalytic and physico-mechanical characteristics. As an alter-native to the known technology for producing oxide catalysts from precursors of metal hydroxocarbonates, there have been selected a manner in which the precursor is copper/zinc hydroxocarbonate. It has been shown that of the many salts obtained from precursors — metal hydroxocarbonates, copper/zinc double hydroxocar-bonate with an aurichalcite structure is most effective. The decomposition of these compounds results in the formation of nanosized metal copper clusters, which have a high specific surface area and high activity in the redox reaction of carbon monoxide conversion with water vapor to produce hydrogen. The coprecipitation conditions and the structure of copper/zinc hydroxocarbonate determine the subsequent activity of the oxide catalyst. A technology for producing nanocatalysts for low-temperature conversion of carbon monoxide with a low (up to 20% — from 54 to 34 wt.%) сopper content was proposed and the conditions for obtaining a pre-cursor and catalyst were optimized.
Keywords: Aurichalcite; catalysts; conversion; copper content; low temperature; metal hydroxocarbonates